Representation Of Literary Devices In Literary Translation - Ruzmetova Maftuna (International Journal Of Literature And Languages, 2025)
The translation of literary texts extends beyond simple linguistic substitution; it involves a deep engagement with the stylistic and cultural layers embedded in the source language. Among the most critical components of this complexity are literary devices, which include metaphor, irony, symbolism, alliteration, hyperbole, and others. This paper explores the challenges and strategies involved in representing literary devices in translation, with a focus on English to Uzbek and English to Russian literary works. By examining select examples and translation strategies, the study aims to reveal the translator's role as a cultural mediator and creative interpreter.